A modified complex modal testing technique for a rotating tire with a flexible ring model. (August 2015) - Lee, Jongsuh; Wang, Semyung; Pluymers, Bert; Desmet, Wim; Kindt, Peter
Abstract: Natural frequencies, mode shapes and modal damping values are the most important parameters to describe the noise and vibration behavior of a mechanical system. For rotating machinery, however, the directivity of the propagation wave of each mode should also be taken into account. For rotating systems, this directivity can be determined by complex modal testing. In this paper, a rolling tire is represented as a flexible ring model. The limitation of application of the complex modal testing which requires two directional measurements at a certain point, which is difficult to measure in practice, has been overcome through a modified complex modal testing which requires only one directional measurements at any two points. The technique is described in detail and applied to both a numerical example and to an experimental data set of a real rotating tire.